The mediating effect of customer satisfaction on the relationship between service quality and customer loyalty in Digital Banking - Gayathri, Dr.S.; Dr.Rekhapriyadharshini, (The journal of contemporary issues in business and government, 2022)
Banks play a significant role inbolstering the Indian economy. People in all walks of life, from the elite class to the people below poverty line, access banks for various financial needs. Providing an array of services, the banking sector has undergone radical changes. The digital transformation had also smitten the banking sector and there is seamless integration of technology at various levels. However, there is the question of customer loyalty associated with these services. Banks today are completely customer centric and the customer has a wide choice to choose from. The customer expects a hassle free service anywhere and everywhere. Security and speed are the other things; the customer is very particular about. Banks now have the crucial task of identifying the customer needs, designing the service deliverables, satisfying them and retaining them. Any detour from the customer’s expectations would lead to customer switch over.